Cardiopulmonary Exercise Capacity and Preoperative Markers of Inflammation - Pervez Sultan; Mark R. Edwards; Ana Gutierrez del Arroyo; David Cain; J. Robert Sneyd; Richard Struthers; Gary Minto; Gareth L. Ackland (Hindawi Limited, 2014)
Explanatory mechanisms for the association between poor exercise capacity and infections following surgery are underexplored. We hypothesized that aerobic fitness-assessed by cardiopulmonary exercise testing (CPET)-would be associated with circulating inflammatory markers, as quantified by the neutrophil-lymphocyte ratio (NLR) and monocyte subsets. The association between cardiopulmonary reserve and inflammation was tested by multivariable regression analysis with covariates including anaerobic threshold (AT) and malignancy. In a first cohort of 240 colorectal patients, AT was identified as the sole factor associated with higher NLR (P=0.03) and absolute and relative lymphopenia (P=0.01). Preoperative leukocyte subsets and monocyte CD14+ expression (downregulated by endotoxin and indicative of chronic inflammation) were also assessed in two further cohorts of age-matched elective gastrointestinal and orthopaedic surgical patients. Monocyte CD14+ expression was lower in gastrointestinal patients (n=43) compared to age-matched orthopaedic patients (n=31). The circulating CD14+CD16− monocyte subset was reduced in patients with low cardiopulmonary reserve. Poor exercise capacity in patients without a diagnosis of heart failure is independently associated with markers of inflammation. These observations suggest that preoperative inflammation associated with impaired cardiorespiratory performance may contribute to the pathophysiology of postoperative outcome.